The Prophethood and the “Khatam al-Nabiyyin” Within the Qur’anic Perspective - Muhammad Darwis Hude (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
Both the term  prophet  and messenger are used in Al- Qur’an, either  concurrently  or  respectively on  its own. The two terms indeed have been long debated by Islamic scholars if there is any distinction between them. Some say there is a definite difference between the two, while some others insist they are a distinction wit- hout a difference but in meaning. Irrespective of the differences, the Islamic scholars agreed that all the prophets and messengers have one same message to convey from the beginning, that is the call to worship one God only. They are on the opinion that there is no hu- man theological evolution ever happened like it was claimed by those who believe in the evolution theory. They assure human belief system remains the same from the day one the religion was known, that is monotheistic in concept. Should there be any difference from one to another, it is all about the syariah tenets that each messenger or prophet brought with them. Obviously, the tenets developed from time to time and came to its perfection under the era of the prophet of Muhammad peace be upon him. Thus, it is unanimously agreed among the Islamic scholar that Muhammad peace be upon him is the final prophet and messenger and the seal of the prophethood.